Economic consequences of firms’ depreciation method choice: Evidence from capital investments - Jackson, Scott B.; (Kelvin) Liu, Xiaotao; Cecchini, Mark (Journal of Accounting and Economics, 2009)
This study identifies several interrelated reasons why firms’ depreciation method choice is likely to influence managers’ capital investment decisions. We find that firms that use accelerated depreciation make significantly larger capital investments than firms that use straight-line depreciation. Further, we find that there has been a migration away from accelerated depreciation to straight-line depreciation over the past two decades. Firms that make such accounting changes make smaller capital investments in the post-change periods than in the pre-change periods. These results suggest that a choice made for external financial reporting purposes influences managers’ capital investment decisions.